A high-temperature adhesive for stainless steel 304: Effect of Cr growth at the interface of alkali silicate adhesive. (July 2022) - Shim, Gyu Hyeon; Kweon, Boyeon; Ji, Min Ki; Jun, Tea-Sung; Ahn, Ho Seon
Abstract: With the recent advancements in the aerospace industry, the demand for adhesive materials with resistance to high temperatures has increased. Although the existing organic adhesive materials have a high adhesion strength, their heat resistance and pyrolysis temperature are low, thus limiting their application under high-temperature conditions. Therefore, we attempted to bond stainless steel 304 using an alkali silicate, an inorganic material-based adhesive with high heat resistance but low adhesive strength and analyzed the effects of surface oxidation of stainless steel 304 on its adhesion strength. The surface treatment of SUS304 was performed using mechanical polishing (MP) and electropolishing (EP). A Cr2 O3 dominant layer (CODL) and a Fe2 O3 dominant layer (FODL) were formed by heat treatment. The adhesion failed in MP, EP, and CODL specimens, when bonding was performed using mixed silicate (MS) because of the differences in thermal expansion coefficients between the metal and glass. FODL and CODL + FODL specimens displayed MS and adhesion strengths of 8.45 MPa and 11.36 MPa, respectively. Each surface and adhesion interface was analyzed through X-ray diffraction (XRD), cross-section scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS), before and after adhesion. When CODL and FODL specimens were placed on both sides to bond with the MS, a needle-like Cr structure appeared on the MS layer from the Cr2 O3 layer that enhanced the mechanical adhesion with the MS and the overall adhesive strength. Based on these findings, we conclude that the adhesion strength can be improved by combining a CODL specimen and a FODL specimen and bonding with glass.